Comprehensive Evaluation of Clinical Roles: Paramedics and Laboratory Specialists - ALKHABIRY, SAMEERAH SALEM HAMZAH; HATTAN, NOURAH ALI AHMAD; ALMALKI, ZAINAB SULAIMAN SHARIF; ALONIZAN, ABLA FAHD MUBARAK; ALQATTAN, HANADI ALI TAHER; ALQURAISH, ALI HASSAN ABDULLAH; AL ZAHRANI, ABDULLAH ALI MOHAMMED; ALROUGI, KHALED AREF; ALMUTAIRI, ABDULRAHMAN MUWAYS; QAYSI, ABDULMAJEED ABDULLAH MOHAMMED; ALOTAIBI, MASHAN FAEH ALI; MUHILL, NAJAH; et al. (Journal of Posthumanism, 2024)
paramedics and laboratory specialists face shared challenges—workload, training gaps, and ethical pressures—but also opportunities through technology, collaboration, and policy innovation. By prioritizing continuous education, robust quality control, and strong ethical frameworks, these professions will thrive in future healthcare landscapes (Reddy & Siqueiros, 2021; Morris, 2023). Their integrated roles will ensure that patient care remains immediate, precise, and ethically grounded, embodying the best of modern medicine.